Online Tools for Strengthening Remote Teaching-Learning in the Times of Emergencies-COVID-19 - M.Padmaja, K.V.Ramana Reddy (International Journal of Advanced Science and Technology, 2020)
COVID-19 is a pandemic which disrupted the world's economy; however, on the other hand, helped in bringing reforms in traditional educational practices. Many changes emerged in the Education System, and one such change is the method of dissemination of education, which had to undergo rapid transformation, that is to adapt to Online System of Teaching, integrating a Traditional Classroom with Online Elements to avoid delays in the Academic Schedules. The teaching community had no choice but to explore some of the new tools and focus on techniques that could make them a competent instructor and also make sure that the students are prepared for Online Classes. The higher education institutions are looking for online tools to continue teaching-learning process without interruption. This paper highlights details of various online software's which can be effectively used in teaching, learning, and evaluation processes.